Clinical predictors of survival in men with castration‐resistant prostate cancer: Evidence That Gleason Score 6 Cancer Can Evolve to Lethal Disease. Issue 16 (29th May 2013) - Nakabayashi, Mari; Hayes, Julia; Taplin, Mary‐Ellen; Lefebvre, Patrick; Lafeuille, Marie‐Helene; Pomerantz, Mark; Sweeney, Christopher; Duh, Mei Sheng; Kantoff, Philip W.
Abstract : BACKGROUND: This study sought to characterize Modern patients with castration‐resistant prostate cancer (CRPC) and identify pretreatment clinical predictors of survival. METHODS: A cohort of men with CRPC with and without metastases (M) treated with secondary hormonal therapy (2eHT) and/or chemotherapy (CT) was identified from the authors' institutional database. Associations of patient and disease characteristics at diagnosis, at androgen‐deprivation therapy (ADT) initiation, at CRPC index date, and survival were evaluated. CRPC index date was defined as the start date of either 2eHT or CT, whichever came first. RESULTS: In the cohort of 622 men, 434 men (70%) had M‐positive disease; 552 men (89%) received 2eHT and 70 men (11%) received CT as their initial CRPC treatment. There were 410 deaths (66%) at the time of analysis. Median overall survival (OS) was 35 months (quartile 1, quartile 3: 21 months, 61 months). In multivariate analyses, higher biopsy Gleason score, the presence of M at ADT initiation, shorter time from ADT start to CRPC, higher prostate‐specific antigen and poorer Eastern Cooperative Oncology Group performance status at CRPC and M at CRPC were predictive of shorter OS. Interestingly, whereas some men with biopsy Gleason scores of 6 died of their disease (N = 42), they had a longer OS after CRPC compared with those with a Gleason score ≥ 7. CONCLUSIONS: This large retrospective study of patients with CRPC in a tertiary cancer center shows that biopsy Gleason score of 6 is associated with a less aggressive CRPC course, and the impact that M at ADT initiation and CRPC have on outcome is quantified. Cancer 2013;119:2990—2998 . © 2013 American Cancer Society . Abstract : Clinical predictors of overall survival in patients with modern castration‐resistant prostate cancer (CRPC) at a large tertiary cancer center were investigated. Biopsy Gleason 6 cancer can progress to CRPC; however, it was associated with a less aggressive CRPC course.